1, 1 '‐Bicyclopropyl‐2, 2‐dicarboxylate and Cyclopropylmethylidenemalonate as Homovinylogs and Vinylogs of Donor‐Acceptor Cyclopropanes. Issue 20 (9th December 2016) - Denisov, Dmitry A.; Novikov, Roman A.; Potapov, Konstantin V.; Korolev, Victor A.; Shulishov, Evgeny V.; Tomilov, Yury V.
Abstract: A new approach was suggested for the development of new carbon‐based synthons on donor‐acceptor cyclopropane (DAC) basis, that are more complex than the usual cyclopropane ring, while maintaining the principle of separation of donor and acceptor substituents in the molecule. This approach is based on expansion of the reactive cyclopropane ring system in DACs by inserting into the structure the additional reactive C−C double bond or the second cyclopropane ring between donor and acceptor substituents. Within this approach and applying a set of procedures adopted in cyclopropane chemistry, the new (2‐phenylcyclopropyl)methylidenemalonate (3 ) and related 2 '‐phenylbicyclopropyl‐1, 1‐dicarboxylate (2 ) were synthesized as vinylog and homovinylog of donor‐acceptor cyclopropanes. Upon studying their reactivity, focusing on their transformations in the presence of various Lewis acids, the bicyclopropyl skeleton in2 behaved as a single six‐carbon synthon, in which both cyclopropane rings reacted in tandem furnishing various products with opening of the cyclopropane rings. On the other hand, the vinylcyclopropane3 turned out to be much less reactive towards the same Lewis acids. Mechanistic aspects, further transformations of the ring‐opened products and potential synthetic applications of these new reactions in organic synthesis are being discussed as well. Abstract : HighlightA new approach for the development and evolution of new complex donor‐acceptor cyclopropanes chemistry was suggested. It is based on expansion of the reactive cyclopropane ring system in DACs by inserting additional carbon elements. Corresponding "donor‐acceptor bicyclopropyl" and related cyclopropanes were synthesized and their chemistry has been investigated.